A study on health problems among government primary school children in rural area of Kadapa district, Andhra Pradesh - Moola, Ram Sagar Reddy; Biyyala, Renuka; Bhuma, Venkata Ramana (International Journal Of Community Medicine And Public Health, 2019)
Background: “To learn effectively, children need good health” says the World Health Organization’s Expert committee on school health services. Inspite of the primary health care that exists in India, yet it is unable to cover the health needs of school children, especially the primary school children. To know their health status and influencing factors, a study is designed in the rural area of Kadapa district of Andhra Pradesh. Methods: A cross sectional study design was used to assess the health condition of the rural government primary school children at school and socio-demographic data at their home during the period July to December 2016. A sample of 683 children from 20 schools was included in the study. The data was analyzed and inferences were drawn. Results: 38.79% of the rural government primary school children had one or more health problem. Dental problems were found in 21.66% followed by skin problems in 8.05%, nutritional defects in 7.61%, eye disorders in 6.88% and ENT problems in 22.84%. Only 5.42% had good personal hygiene. Majority of the children were poor belonging to the socioeconomic status of class IV (19.62%) and class V (76.60%). 83.39% of the children with health problems had poor housing conditions. Conclusions: More than 2/3rd was found suffering from health problem which was almost equally distributed among boys and girls. The suffering children were almost 95% from lower socioeconomic status and 83% with poor housing conditions.